"Branding Bildung": Commodifying the Uniqueness of Popular Education. Issue 2 (May 2021) - Fejes, Andreas; Aman, Robert; Nyström, Sofia
Popular education has a long history in Sweden, dating back to the mid-1800s and having developed in close relationship with the state. This relationship has been sustained over the years by the way popular education is spoken of as being "unique"—as being complementary to formal education. In this article, we focus on how the uniqueness of popular education is shaped today, and how it operates to legitimize further support. We draw on Barthes' notion of myth, analyzing interviews with managers, principals, study circle leaders and teachers working with adult asylum seekers and refugees at study associations and folk high schools. We argue that the myth of the uniqueness of popular education is made up of three rhetorical figures that are mobilized by a range of actors legitimizing state support for popular education. The myth thus becomes a "tool" that commodifies popular education, that is, that turns the myth into monetary funds.